EFFECT OF PRETREATMENTS IN GERMINATION SEEDS Pistacia Khinjuk . (STOCK) AND SEEDLING GROWTH. - J. ALAshoo (Mesopotamia Journal of Agriculture)
This study was occurred in the Forestry Department to investigate the storage scarification and pre-chilling in germinating seeds and seedling growth . The results revealed superior seedling grouth from unstorage seeds . And giving highest average of in all character studied . Also the scarification seeds superiority in all character except the stem length and giving hightest germination percentage 25.74 % . Number of leaves 15.16 and dry weight of the stem and leaves 0.92 gm . 1.46 gm . The periods of the chilling . The chilling 48 hour was superior in all characters and gave highest germination percentage 32.18 % . stem length12.98 cm . number of leaves 17.41 and dry weight of stem and leaves 0.67 gm . 1.72 gm . The interaction between unstorage and scarification . the interaction between storage and chilling . interaction between unstorage and chilling 48 hour and storage chilling 48 hour . The interaction scarification and chilling 48 hour were the best in all characters .